IMPLEMENTASI METODE OUTDOOR STUDY DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM PADA HASIL DAN MOTIVASI BELAJAR SISWA KELAS IV SD NEGERI GEDANGANAK 02 UNGARAN - Dwi Kurnianti Fajar Cahyadi, dan M. Yusuf Setia Wardana (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
Abstract            This research was motivated by the low results and learning motivation of the fourth grade students of SD Negeri Gedanganak 02 Ungaran in Natural Sciences (IPA). Lack of varied learning methods in teaching and learning activities in the classroom. The formulation of the problem in this study is how the effectiveness of the Outdoor Study method on the results and motivation to learn in the fourth grade of the Gedanganak State Elementary School 02 Ungaran 2018/2019 academic year. This study aims to find out and analyze the effectiveness of outdoor learning methods on the results and learning motivation of fourth grade students of SD Negeri Gedanganak 02 Ungaran.This type of research is quantitative in the form of Pre Experimental Design in the form of One Group Pretest-Posttest Design. The study population was fourth grade students of SD Negeri Gedanganak 02 Ungaran 2018/2019 school year with a total of 25 students. The population in this study were all fourth grade students of SD Negeri Gedanganak 02 Ungaran which numbered 25 students using saturated sample techniques. The documentation in this study were obtained through observation, questionnaires, and documentation. The results of this study indicate that the outdoor study method proved effective against the results ability and learning motivation of fourth grade students of SD Negeri Gedanganak 02 Ungaran with the average scores of pretest 60.2 and the posttest obtaining an average value of 75.6. The t test obtained by tcount> t table is 10.282> 2.064 then Ha is accepted. So that it can be concluded the outdoor study method on the results and learning motivation of fourth grade students of SD Negeri Gedanganak 02 Ungaran.Keywords: outdoor study method, learning motivation, learning outcomes